Un-triggering the jurisdiction of the International Criminal Court : the Ugandan Referral of the situation concerning the Lord’s Resistance Army in Northern Uganda to the International Criminal Court - Akonumbo, Atangcho Nji (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.